Correlation Between use of Hormonal Contraception Depo Medroxyprogesterone Type and Acetate Injectable Type changes in body weight on family planning acceptors - Hamang, Sitti Hadriyanti; S, Suryanti; Karuniawati, Nia (An Idea Health Journal, 2024)
Efforts to create a prosperous society and create a quality family include controlling the number of births, regulating, spacing or limiting pregnancies by participating in a family planning program. This research method uses a survey with a cross-sectional study method with a sample size of 64 respondents, then a literature review is carried out then continued with planning and data collection. Based on the Mann-Withney test, it shows a p value of 0.036, indicating that there is a relationship between the use of depo medroxy progesterone acetate injectable contraception and changes in body weight in family planning acceptors at BPM Patmawati.